Uji Efektivitas Model Self Management Education for Pregnancy Risk (SMEERI) dalam Meningkatkan Kemampuan Diri Deteksi Dini Tanda Bahaya Kehamilan - Nisma Nisma; Diena Juliana; Nurul Hidayah; Fitriah Fitriah (Malahayati Nursing Journal, 2024)
ABSTRACT Pregnancy complications are one of the health problems that contribute to an increase in the prevalence of deaths during pregnancy, childbirth and the postpartum period. The ability to detect early pregnancy risks and danger signs is needed to know more quickly whether the mother is experiencing risks in her pregnancy. This study aims to test the effectiveness of the self management education for pregnancy risk (SMEERI) model in improving the ability to detect early pregnancy risks and danger signs during the pregnancy period of mothers.  The design used in this study will test the SMEERI model using a quantitative study with a quasi experiment design and a pre and post one group design. Based on the results of the paired t test, the p-value is 0.000. This shows the effectiveness of the SMEERI method in improving the mother's ability to detect early pregnancy danger signs.There is a difference in the average ability of mothers to detect early signs of danger of pregnancy before and after the SMEERI model. The SMEERI model effectively improves the ability of mothers in early detection of pregnancy danger signs. Keywords: Self Management Education, Early Detection, Pregnancy Danger Signs  ABSTRAK Komplikasi kehamilan menjadi salah satu diantara masalah kesehatan yang menyumbangkan peningkatan prevalensi kematian selama masa kehamilan, persalinan dan masa nifas. Kemampuan deteksi dini risiko dan tanda bahaya kehamilan sangat diperlukan untuk mengetahui lebih cepat apakah ibu mengalami risiko pada kehamilannya. Penelitian ini bertujuan untuk menguji efektivitas model self management education for pregnancy risk (SMEERI) dalam meningkatkan kemampuan deteksi dini risiko dan tanda bahaya kehamilan selama masa periode kehamilan ibu. Berdasarkan hasil uji paired t test diperoleh nilai p-value sebesar 0.000. hal ini menunjukan efektifitas metode SMEERI efektif meningkatkan kemampuan ibu dalam deteksi dini tanda bahaya kehamilan . Terdapat perbedaan rata-rata kemampuan ibu deteksi dini tanda bahaya kehamilan sebelum dan sesudah pemberian model SMEERI. Model SMEERI efektif meningkatkan kemampuan ibu dalam deteksi dini tanda bahaya kehamilan. Kata Kunci: Self Management Education,  Deteksi Dini, Tanda Bahaya Kehamilan